Catalytic Formation of Acrylate from Carbon Dioxide and Ethene. Issue 38 (12th August 2014) - Hendriksen, Coen; Pidko, Evgeny A.; Yang, Gang; Schäffner, Benjamin; Vogt, Dieter
Abstract With regard to sustainability, carbon dioxide (CO2) is an attractive C1 building block. However, due to thermodynamic restrictions, reactions incorporating CO2 are relatively limited so far. One of the so‐called "dream reactions" in this field is the catalytic oxidative coupling of CO2 and ethene and subsequent β‐H elimination to form acrylic acid. This reaction has been studied intensely for decades. However up to this date no suitable catalytic process has been established. Here we show that the catalytic conversion of ethene and CO2 to acrylate is possible in the presence of a homogeneous nickel catalyst in combination with a "hard" Lewis acid. For the first time, catalytic conversion of CO2 and ethene to acrylate with turnover numbers (TON) of up to 21 was demonstrated.